Erectile Dysfunction Following Intravitreal Bevacizumab - Yohendran, Jayshan (Medknow Publications, 2010)
Despite initial concerns regarding systemic complications, the use of intravitreal antivascular endothelial growth factor (anti-VEGF) agents for ocular disease is rapidly expanding worldwide, in terms of both the number of patients injected and its indications. To our knowledge, there are no cases in the literature reporting erectile dysfunction following the use of intravitreal bevacizumab. We postulate an organic mechanism for impaired erectile function due to systemically absorbed intravitreal bevacizumab. We describe a case of erectile dysfunction following intravitreal bevacizumab administration. Color fundus photos, fluorescein angiogram and optical coherence tomography images are presented. A 40-year-old male underwent intravitreal bevacizumab therapy for macular edema secondary to a branch retinal vein occlusion. He subsequently developed transient erectile dysfunction after each of his two bevacizumab injections. His only comorbidity was mild hypertension. Erectile dysfunction may be a side effect of intravitreal bevacizumab. The erectile dysfunction could be organic and/or psychogenic in etiology.